Design and fabrication of a wideband CMOS continuous-time integrated baseband active filter for a synthetic aperture radar receiver - Faizah Abu Bakar (School of Microelectronic Engineering, 2016)
This research work is to design and fabricate a low-pass continuous-time integrated baseband filter circuit with cutoff frequency of 50 MHz up to 160 MHz as part of a fully integrated Synthetic Aperture Radar (SAR) receiver. The filter should exhibit passband ripple from ±0.5 dB to ±1 dB as a standalone circuit and -20 dB attenuation at 220 MHz. The integrated low-pass filter to be designed is targeted to provide gain of 20% to 30% percent from the whole baseband gain. Measurements of the filter (baseband) as a standalone structure are to be done in order to show the functionality of the filter and the feasibility of it to comply the specifications of the filter circuit alone. Then, the filter is going to be measured together with the other receiver building blocks in different temperatures to demonstrate the functionality of the filter and the feasibility of it to fulfil the specifications of a complete integrated SAR receiver in a different environment.